Modulation of T-bet and Eomes during Maturation of Peripheral Blood NK Cells Does Not Depend on Licensing/Educating KIR - Pradier, Amandine; Simonetta, Federico; Waldvogel, Sophie; Bosshard, Carine; Tiercy, Jean-Marie; Roosnek, Eddy (Frontiers in Immunology, 2016)
Peripheral NK cells upregulate T-bet and downregulate Eomes, the key transcription factors regulating NK cell maturation and function during the last maturation steps toward terminally differentiated effector cells. During this process, NK cells acquire killer immunoglobulin-like receptors (KIR) and effector functions such as cytotoxicity and target cell induced cytokine production. Inhibitory KIR are pivotal in the control of effector functions but whether they also modulate T bet/Eomes expression is unknown. We have measured T-bet/Eomes levels, KIR-expression and effector functions of maturing CD94negCD56dimNK cells using CD57 as surface marker for maturation. Our cohort consisted of 23 healthy blood donors (HBD) homozygous for the KIR A haplotype that contains only inhibitory KIR2DL1 (ligand HLA-C2), KIR2DL3 (ligand HLA-C1) and KIR3DL1 (ligand HLA-Bw4). We confirm that during maturation of NK cells, the number of KIR increases, levels of T-bet/Eomes are modulated and that cells acquire effector functions such as cytotoxicity (CD107) and target cell induced cytokine production (TNF-α). Because maturation was associated with the increase of the number of KIR as well as with the modulation of T bet/Eomes, the number of KIR correlated with the extent of T-bet/Eomes modulation. However, whether the KIR were triggered by their cognate HLA ligands or not had no impact on T-bet and Eomes expression indicating that modulation of T-box transcription factors during NK cell maturation does not depend on signals conveyed by KIR. We discuss the relevance of this finding in the context of models of NK cell maturation while cautioning that results obtained in a perhaps quite heterogeneous cohort of HBD are not necessarily conclusive.